Ex Post Voluntary Disclosure Strategies for Insiders* - Levine, Carolyn B.; Smith, Michael J. (Contemporary Accounting Research, 2003)
Abstract Asymmetric information between corporate insiders and other market participants can lead to large bid‐ask spreads or even a collapse of trade in financial markets. In this paper, we discuss how voluntary disclosure by insiders can remedy this problem. When insiders make disclosure decisions after they become informed, other market participants update their prior beliefs on the basis of both the information disclosed and the information not disclosed. Insiders then give up some or all of their information advantage to weakly increase their profits. These results do not rely on ex ante commitments on the part of the insiders.